(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the impact of branches of foreign universities in Uzbekistan on the development of the country’s educational system. It highlights the advantages brought about by the presence of these institutions, including access to world-class resources, cultural exchange, and innovation stimulation. The article emphasizes the importance of fostering partnerships between foreign and local stakeholders while acknowledging the challenges such collaborations may pose. Overall, it underscores the significant role played by foreign university branches in enhancing the quality and global competitiveness of higher education in Uzbekistan.